Tinjauan Hukum Islam, Hukum Internasional dan Perundang-Undangan tentang Pelaku Lesbian, Gay, Biseks, dan Transgender (LGBT) - Abd. Raziq; Jumadil; Arsul Maddupe; Safaruddin (Program Studi Hukum Keluarga Islam (Ahwal Syakhshiyyah), Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
This study aims to find out the views of Islamic law, international law, and legislation regarding the law of LGBT actors in the type of literature research using a normative juridical approach. The source of data used in this study is primary data collected by reading official documents such as the Al-Qur'an, Hadith, Fiqh, and national and international laws and regulations. Data collection techniques through documents such as the Al-Qur'an and Hadith as well as laws and regulations. The view of Islamic law towards LGBT is that the law is unlawful because it violates human nature, the punishment is the same as for adultery, although some scholars punish Ta'zir (submitted to the government).